Difference between revisions of "009B Sample Midterm 3, Problem 4"
Jump to navigation
Jump to search
(Created page with "<span class="exam">Evaluate the integral: ::<math>\int \sin (\ln x)~dx.</math> {| class="mw-collapsible mw-collapsed" style = "text-align:left;" !Foundations: |- |'...") |
|||
Line 1: | Line 1: | ||
− | <span class="exam"> | + | <span class="exam"> The rate of reaction to a drug is given by: |
− | ::<math> | + | ::<math>r'(t)=2t^2e^{-t}</math> |
+ | |||
+ | <span class="exam">where <math style="vertical-align: 0px">t</math> is the number of hours since the drug was administered. | ||
+ | |||
+ | <span class="exam">Find the total reaction to the drug from <math style="vertical-align: -1px">t=1</math> to <math style="vertical-align: 0px">t=6.</math> | ||
Line 7: | Line 11: | ||
!Foundations: | !Foundations: | ||
|- | |- | ||
− | | | + | |If we calculate <math style="vertical-align: -14px">\int_a^b r'(t)~dt,</math> what are we calculating? |
|- | |- | ||
− | | | + | | |
+ | We are calculating <math style="vertical-align: -5px">r(b)-r(a).</math> This is the total reaction to the | ||
|- | |- | ||
| | | | ||
− | + | drug from <math style="vertical-align: 0px">t=a</math> to <math style="vertical-align: 0px">t=b.</math> | |
|} | |} | ||
+ | |||
'''Solution:''' | '''Solution:''' | ||
Line 19: | Line 25: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | | | + | |To calculate the total reaction to the drug from <math style="vertical-align: -1px">t=1</math> to <math style="vertical-align: -4px">t=6,</math> |
|- | |- | ||
− | | | + | |we need to calculate |
− | |||
− | |||
|- | |- | ||
| | | | ||
− | + | <math>\int_1^6 r'(t)~dt=\int_1^6 2t^2e^{-t}~dt.</math> | |
|} | |} | ||
Line 32: | Line 36: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | | | + | |We proceed using integration by parts. |
+ | |- | ||
+ | |Let <math style="vertical-align: 0px">u=2t^2</math> and <math style="vertical-align: 0px">dv=e^{-t}dt.</math> | ||
|- | |- | ||
− | | | + | |Then, <math style="vertical-align: -1px">du=4t~dt</math> and <math style="vertical-align: 0px">v=-e^{-t}.</math> |
|- | |- | ||
− | | | + | |Then, we have |
|- | |- | ||
− | | | + | | <math style="vertical-align: -14px">\int_1^62t^2e^{-t}~dt=\left. -2t^2e^{-t}\right|_1^6+\int_1^6 4te^{-t}~dt.</math> |
− | |||
− | |||
− | |||
− | |||
− | |||
|} | |} | ||
Line 49: | Line 50: | ||
!Step 3: | !Step 3: | ||
|- | |- | ||
− | | | + | |Now, we need to use integration by parts again. |
|- | |- | ||
− | | | + | |Let <math style="vertical-align: 0px">u=4t</math> and <math style="vertical-align: 0px">dv=e^{-t}dt.</math> |
|- | |- | ||
− | | | + | |Then, <math style="vertical-align: -1px">du=4dt</math> and <math style="vertical-align: 0px">v=-e^{-t}.</math> |
− | |||
|- | |- | ||
− | | | + | |Thus, we get |
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
− | + | \displaystyle{\int_1^62t^2e^{-t}~dt} & = & \displaystyle{\left. -2t^2e^{-t}-4te^{-t}\right|_1^6+\int_1^6 4e^{-t}}\\ | |
− | + | &&\\ | |
− | + | & = & \displaystyle{\left. -2t^2e^{-t}-4te^{-t}-4e^{-t}\right|_1^6}\\ | |
− | | | + | &&\\ |
− | + | & = & \displaystyle{-2(6)^2e^{-6}-4(6)e^{-6}-4e^{-6}}-(-2(1)^2e^{-1}-4(1)e^{-1}-4e^{-1}) \\ | |
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{-100+10e^5}{e^6}.} | ||
+ | \end{array}</math> | ||
|} | |} | ||
+ | |||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Final Answer: | !Final Answer: | ||
|- | |- | ||
− | | <math>\frac{ | + | | <math>\frac{-100+10e^5}{e^6}</math> |
|} | |} | ||
[[009B_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']] | [[009B_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']] |
Revision as of 11:20, 9 April 2017
The rate of reaction to a drug is given by:
where is the number of hours since the drug was administered.
Find the total reaction to the drug from to
Foundations: |
---|
If we calculate what are we calculating? |
We are calculating This is the total reaction to the |
drug from to |
Solution:
Step 1: |
---|
To calculate the total reaction to the drug from to |
we need to calculate |
|
Step 2: |
---|
We proceed using integration by parts. |
Let and |
Then, and |
Then, we have |
Step 3: |
---|
Now, we need to use integration by parts again. |
Let and |
Then, and |
Thus, we get |
|
Final Answer: |
---|